The Effect of Good Government Governance on Developing Village Index (IDM) Through Sustaianable Development Goals (SDGS) (Empirical Study In Kedungjati District, Grobogan Regency) - Afandi, Pandi; Puspita, Maria Entina; Wibowo, Mada Adi; Kusumaningrum, Diah; Santoso, Ahmad (Global Health Science Group, 2023)
The study aims to analyze the effect of good government governance (GGG) and sustainable development goals (SDGs) and their implications on the village development index (IDM) of villages in Kedungjati District, Grobogan Regency with explanatory reaserch. The samples in this study were taken from villagers in 12 villages in Kedungjajati District with non-probability sampling where each village was represented by 3 village community leaders who understood the conditions of their village development. The results of the study showed. GGG has a significant effect on SGDs and SDGs have a significant effect on IDM, while GGG has no significant effect on IDM, for SGDs has a greater influence than the influence of GGG on IDM, the SGDs variable has proven not to be a connecting variable between GGG and village IDM in Kedungjati District, Grobogan Regency. Looking at the results of this study, the factor of good governance or GGG in its implementation needs serious attention in order to be able to realize the success of village development, as well as the need for the selection and placement of intervening variables that are more in accordance with the character of the object and research problems such as variability of village competitiveness, village development performance and other variables that are more relevant.